Uterine Fibroid Symptom - Quality of Life questionnaire translation and validation into Brazilian Portuguese - Rita Oliveira da Silva; Mariano Tamura Vieira Gomes; Rodrigo de Aquino Castro; Cláudio Emílio Bonduki; Manoel João Batista Castello Girão (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Purpose To translate into Portuguese, culturally adapt and validate the Uterine Fibroid Symptom - Quality of Life (UFS-QoL) questionnaire for Brazilian women with uterine leiomyoma. Methods Initially, the UFS-QoL questionnaire was translated into Brazilian Portuguese in accordance with international standards, with subsequent cultural, structural, conceptual and semantic adaptations, so that patients were able to properly answer the questionnaire. Fifty patients with uterine leiomyoma and 19 patients without the disease, confirmed by abdominal pelvic examination and/or transvaginal ultrasound, were selected at the outpatient clinics of the Department of Gynecology of the Universidade Federal de São Paulo (Unifesp). The UFS-QoL questionnaire was administered to all women twice on the same day, with two different interviewers, with an interval of 15 minutes between interviews. After 15 days, the questionnaire was readministered by the first interviewer. Reliability (internal consistency and test-retest), construct and discriminative validity were tested to ratify the questionnaire. Results The reliability of the instrument was assessed by Cronbach's α coefficient with an overall result of 0.97, indicating high reliability. The survey results showed a high correlation (p= 0.94; p 0.001). Conclusion The UFS-QoL questionnaire was successfully adapted to the Brazilian Portuguese language and Brazilian culture, showing reliability and validity.